Effect of modified early obstetric warning system (MEOWS) on mode of delivery and neonatal outcomes - Herlina, Nina; Taufik, Afifah; Ekowati , Erik; Jubaedah, Ade; Astuti, Mozha Desri Puji (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2025)
Delayed management of obstetric complications increases maternal and neonatal mortality rates. The Modified Obstetric Early Warning System (MEOWS) facilitates early detection, determines safe delivery, and improves neonatal outcomes, especially when combined with obstetric factors. This study aims to analyze the effect of MEOWS implementation on the delivery mode and neonatal outcomes, both individually and in combination with obstetric factors. This study used an observational analytical method with a cross-sectional design. Data were collected from the medical records of 281 patients who gave birth at Bhayangkara Brimob Hospital in 2024. Sampling used probability sampling with proportional stratified random sampling. The independent variable was MEOWS, the dependent variables were delivery mode and neonatal outcomes, while obstetric factors were considered confounding variables. Bivariate analysis used chi-square and Fisher's exact tests. Multivariate analysis used binary logistic regression. Bivariate results: MEOWS was linked significantly to neonatal outcomes, but not with delivery mode. Multivariate analysis: MEOWS had no significant effect on delivery mode and neonatal outcomes (p>0.05). Delivery Mode was significantly associated with parity (p = 0.012; OR 2.073) and history of previous delivery (p < 0.001; OR = 4.858). Meanwhile, neonatal outcomes were significantly associated with gestational age and parity (p<0.05; OR 45.49 vs OR 0.171). The application of MEOWS combined with obstetric factors improves the prediction of complications, guides clinical decisions, reduces unnecessary interventions, and contributes to better outcomes. Further research is recommended to develop an integrated risk prediction model to improve the accuracy of assessment and enhance safety for both mothers and newborns.